2016
DOI: 10.3389/fpls.2016.01331
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Performance of Diverse Frankia Strains on Salt-Stressed Casuarina glauca and Casuarina equisetifolia Plants

Abstract: Symbiotic nitrogen-fixing associations between Casuarina trees and the actinobacteria Frankia are widely used in agroforestry in particular for salinized land reclamation. The aim of this study was to analyze the effects of salinity on the establishment of the actinorhizal symbiosis between C. glauca and two contrasting Frankia strains (salt sensitive; CcI3 vs. salt tolerant; CeD) and the role of these isolates in the salt tolerance of C. glauca and C. equisetifolia plants. We show that the number of root nodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 71 publications
(107 reference statements)
1
28
0
1
Order By: Relevance
“…Similarly to what occurs in legume–rhizobia symbioses, it has been reported that inoculation with the microsymbiont Frankia improves the host plant salinity tolerance (Reddell et al, 1986; Ng, 1987; Oliveira et al, 2005; Ngom et al, 2016a). Frankia strains CcI3 and CeD significantly improved Casuarina glauca and Casuarina equisetifolia plant growth, shoot, root, and total dry weight, proline and chlorophyll contents according to the symbiotic association (Ngom et al, 2016a). According to Ng (1987), inoculated C. equisetifolia plants exhibited greater growth (shoot, root, and total dry weight) compared to uninoculated plants under saline conditions.…”
Section: Strategies To Improve Salt Tolerance In Cropsmentioning
confidence: 74%
See 2 more Smart Citations
“…Similarly to what occurs in legume–rhizobia symbioses, it has been reported that inoculation with the microsymbiont Frankia improves the host plant salinity tolerance (Reddell et al, 1986; Ng, 1987; Oliveira et al, 2005; Ngom et al, 2016a). Frankia strains CcI3 and CeD significantly improved Casuarina glauca and Casuarina equisetifolia plant growth, shoot, root, and total dry weight, proline and chlorophyll contents according to the symbiotic association (Ngom et al, 2016a). According to Ng (1987), inoculated C. equisetifolia plants exhibited greater growth (shoot, root, and total dry weight) compared to uninoculated plants under saline conditions.…”
Section: Strategies To Improve Salt Tolerance In Cropsmentioning
confidence: 74%
“…Among three Frankia isolates used separately as inoculums of C. glauca , Thr which was more in vitro sensitive to salt stress, was the most effective strain in planta . A recent study showed that inoculation of C. glauca plants with the salt-sensitive CcI3 strain improved plants growth under saline conditions while in C. equisetifolia plants the salt-tolerant strain CeD was more effective (Ngom et al, 2016a). These results suggest there is no correlation between in vitro salt tolerance of Frankia strains and their effectiveness in association with plants under salt stressed conditions (Girgis et al, 1992; Ngom et al, 2016a).…”
Section: Strategies To Improve Salt Tolerance In Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, preliminary growth tests of free-living Frankia Thr in the presence of increasing NaCl concentrations indicated that this strain was indeed salt tolerant, maintaining a normal growth curve at least up to 600 mM NaCl (unpublished data). Also, studies developed by other research groups revealed that despite the fact that salt stress response is rather diverse among Frankia strains in vitro [26], a similar impact of salt stress was observed in C. glauca plants nodulated by "salt tolerant" and "salt sensitive" strains, respectively [9]. In short, the level of salt tolerance in vitro did not predict the level of salt tolerance in planta.…”
Section: Introductionmentioning
confidence: 90%
“…The role of biofertilizers such as rhizobia (Diouf et al, 2005;Thrall et al, 2008), Frankia (Diagne et al, 2013;Ngom et al, 2016), arbuscular mycorrhizal fungi (Evelin et al, 2009;Kohler et al, 2010) and plant growth-promoting rhizobacteria (Paul and Nair, 2008;Kohler et al, 2010) in plants tolerating salt stress has been well established in many studies. The bacterialmycorrhizal-legume tripartite symbiosis is currently being suggested as a possible solution to reforestation (Kohler et al, 2010 ;Diagne et al, 2013;Soliman et al, 2014;Ngom et al, 2016;Zhu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%